Analysis of the Influence of Fixed Asset Depreciation Methods on Profitability: A Case Study of the Tirta Arcamanik Endah Association - Fitria, Salwa Nur; Khotimah, Alifiah (Operations Research: International Conference Series, 2025)
Fixed assets are a significant long-term investment for a company. For Paguyuban Tirta Arcamanik Endah, a company providing artesian water services, fixed assets such as water distribution infrastructure are the backbone of operations. Choosing the right fixed asset depreciation method is crucial, because it will affect the company’s cost recognition, net income, and cash flow. This study aims to test the hypothesis that the use of the declining balance method will increase the company’s cash flow in the short term, but can reduce the long-term profitability of water service providers. This study will analyze the financial report data of Paguyuban Tirta Arcamanik Endah for 2 years, focusing on the effect of the depreciation method on variables such as net income, operating cash flow, and financial ratios. This study is expected to fill the gap in research related to the impact of depreciation methods on medium-scale water service providers. The results of this study can provide recommendations for company management in choosing the optimal depreciation method, as well as contributing to the development of accounting literature.